2017
DOI: 10.1111/aphw.12091
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Well‐Being Training in Healthy Older Adults

Abstract: This pilot study suggests that PWB training can be effective in older adults, with a positive generalisation effect on cognition (WM). The discussion focuses on the need to develop PPIs tailored to older adults' needs and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 70 publications
(90 reference statements)
0
15
0
3
Order By: Relevance
“…Choosing to take action or changing negative thinking, for example, feeling low or sad, indicates that older adults are already using strategies that are successful which could be usefully shared with others (their peers) and could form the basis of peer support training programmes. The strategies used by the participants in our study are similar to, but also complement, the range of interventions that have been tested with older adults to enhance positive emotion and well‐being (Cantarella et al, ; Quoidbach, Berry, Hansenne, & Mikolajczak, ; Smith & Hollinger‐Smith, ). For example, our participants were contributing with acts of kindness, being grateful and savouring, which involved having activities they could look forward to.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Choosing to take action or changing negative thinking, for example, feeling low or sad, indicates that older adults are already using strategies that are successful which could be usefully shared with others (their peers) and could form the basis of peer support training programmes. The strategies used by the participants in our study are similar to, but also complement, the range of interventions that have been tested with older adults to enhance positive emotion and well‐being (Cantarella et al, ; Quoidbach, Berry, Hansenne, & Mikolajczak, ; Smith & Hollinger‐Smith, ). For example, our participants were contributing with acts of kindness, being grateful and savouring, which involved having activities they could look forward to.…”
Section: Discussionmentioning
confidence: 82%
“…Participants had ways of knowing what worked for them. A number of studies have identified how specific psychological interventions can impact positively on older adults' well‐being (Cantarella, Borella, Marigo, & De Beni, , Salces‐Cubero, Ramirez‐Fernadez & Ortega‐Martinez, ). A systematic review of eight studies found that reminiscence interventions were the most prevalent, and less common included life review, self‐management bibliotherapy, with some studies using a combination of approaches, such as gratitude and savouring (Sutipan, Intarakamhang, & Macaskill, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous intervention studies with older adults in the community, clinics, and in nursing homes have reported noticeable improvements in their psychological well-being (30)(31)(32)(33)(34)(35)(36), subjective happiness (36)(37)(38)(39), and life satisfaction (30,40,41). These changes in well-being are accompanied by improvements in the quality of sleep (30,33), better working memory (32), decreased anxiety (36), higher levels of overall mindfulness (42), and improvements in self-reported feelings of depression and depressive symptoms (30, 34-36, 38, 39, 42). Although these well-being interventions suggest that the older population's quality of life can be improved, studies with more rigorous designs and extended follow-up measurements are needed to consolidate these positive findings.…”
Section: Interventionsmentioning
confidence: 99%
“…Atualmente, encontra-se um campo de trabalho grupal marcado pela diversidade de settings, participantes, objetivos, abordagens teóricas e epistemológicas que caracterizam os distintos e inúmeros grupos (Shay, 2017). A despeito desta diversidade, encontra-se um campo de produção científica marcado pela predominância de métodos quantitativos com delineamentos experimentais, cujo enfoque foram os resultados produzidos por determinado grupo em termos de pré e pós-teste (Cantarella, Borella, Marigo, & De Beni, 2017;McFarlane, Burrell, Duggan, & Tandon, 2017;Zlotnick, Tzilos, Miller, Seifer, & Stout, 2016).…”
Section: Introductionunclassified